An outlook on vascular hydrogen sulphide effects, signalling, and therapeutic potential. (28th June 2013) - Popov, Doina
Abstract: Hydrogen sulphide (H2 S) is the most recently discovered gasotransmitter. It is endogenously generated in mammalian vascular cells and attracts substantial interest by its function as physiological relevant signalling mediator, and by its dysfunction in metabolic diseases like obesity, type 2 diabetes and their associated complications. The purpose of this review is to highlight the novel findings on vascular H2 S homeostasis, pathology-associated dysregulation, cell signalling, and therapeutic potential. The data bases searched were Medline and PubMed, from 2008 to 2012 (terms: hydrogen sulphide, sulfhydration). The new reports definitely assess the vasculoprotectant role of H2 S in health, and its reduced biosynthesis/systemic levels in obesity, diabetes, atherosclerosis and hypertension. One of the mechanisms of H2 S signalling discussed here is S-sulfhydration of catalytic cysteine residue of PTP1B, a negative regulator of insulin and leptin signalling. Finally, the review critically evaluates the compounds able to regulate vascular H2 S bioavailability, and with potential in therapeutic exploitation.